1982
DOI: 10.1073/pnas.79.19.6080
|View full text |Cite
|
Sign up to set email alerts
|

Sprouting from chicken embryo dorsal root ganglia induced by nerve growth factor is specifically inhibited by affinity-purified antiganglioside antibodies.

Abstract: The involvement of gangliosides in processes related to nerve regeneration and sprouting has been demonstrated' recently. The type of interaction by which gangliosides may influence neuronal' sprouting was investigated in the present work.Affinity-purified rabbit anti-GMI antibodies were found to block the sprouting from dorsal root ganglia (DRG) of chicken embryo induced by nerve growth factor (NGF). Only a moderately inhibitory effect was produced by antibodies directed to GM2, suggesting a specific interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(27 citation statements)
references
References 29 publications
(41 reference statements)
3
24
0
Order By: Relevance
“…Longitudinal studies will be required to address the question whether clearance of Abs from circulation allows regeneration of inhibited nerve fibers in this model. Overall, this concept of inhibition of axon regeneration through gangliosides is also supported by previous work showing that Abs against GM1 ganglioside can inhibit regeneration in nonmammalian neurons (Schwartz and Spirman, 1982;Sparrow et al, 1984).…”
Section: Discussionsupporting
confidence: 77%
“…Longitudinal studies will be required to address the question whether clearance of Abs from circulation allows regeneration of inhibited nerve fibers in this model. Overall, this concept of inhibition of axon regeneration through gangliosides is also supported by previous work showing that Abs against GM1 ganglioside can inhibit regeneration in nonmammalian neurons (Schwartz and Spirman, 1982;Sparrow et al, 1984).…”
Section: Discussionsupporting
confidence: 77%
“…In fact, although neurite outgrowth has not been evaluated in this study, GM 1 has been reported to facilitate neurite outgrowth in cells both with and without an absolute neuronotrophic requirement for survival and/or neurite extension (Byrne et al, 1983;Ferrari et al, 1983;Facci et al, 1984;KatohSemba et al, 1984;Leon et al, 1984;Matta et al, 1986). Interestingly, in chicken DRG cells in vitro, gangliosides potentiate NGF-induced neurofilament expression and maintenance (Doherty et al, 1985) while antibodies to GM1 block in a dose-dependent manner the NGF-induced neurite outgrowth (Schwartz and Spirman, 1982). In SB21B2 cells, there occurs during ganglioside-induced differentiation a significant increase in the expression of mRNA for tubulin (Rybak et al, 1983).…”
Section: Discussionmentioning
confidence: 72%
“…Hence, a peripheral nerve lesion induces fundamental changes in the chemical phenotype of chemosensitive primary sensory neurons, which express the capsaicin/TRPV1 receptor: these neurons which, in the intact animal do not bind the GM1 ganglioside change their phenotype and, similarly to large DRG neurons, turn into GM1 binding ganglion cells. GM1 plays a critical role in the mechanisms of the trophic actions of growth factors, in particular nerve growth factor (NGF, (Schwartz and Spirman, 1982, Leon et al, 1984, Mutoh et al, 1998)which, in turn, plays a pivotal role in the regulation of the capsaicin sensitivity of DRG neurons . Since in rat sensory ganglion neurons the availability of NGF, and consequently the expression of the capsaicin/TRPV1 receptor is critically dependent on the retrograde axonal transport , Aguayo and White, 1992, Bevan and Winter, 1995, it seemed worthwhile to initiate further studies to reveal possible changes in the expression of the TRPV1 receptor following different types of peripheral nerve lesions.…”
Section: Discussionmentioning
confidence: 99%